Faktor-faktor yang mempengaruhi kepuasan kerja perawat di Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Provinsi Riau - Hilda Oktavianis; Devi Purnamasari; Agus Salim (Politeknik Karya Husada, 2022)
Nursing services are a determining factor for success in hospital health services, because based on data it is stated that in almost every country 80% of health services are provided by nurses. 40% of health care providers in Indonesia are nursing personnel. Given that nurses are one of the important human resources in hospitals, nurses are expected to work professionally and loyally in carrying out their work, resulting in job satisfaction. This study aims to determine the factors that affect the job satisfaction of nurses in Arifin Achmad Hospital, Riau Province. The factors studied in this study were salary factors, interpersonal relations between co-workers and promotion opportunities. This research uses quantitative research. This study uses the dependent variable, namely the job satisfaction of nurses and the independent variables, namely salary, interpersonal relations of co-workers and promotion opportunities by distributing questionnaires via the google form link. The sampling technique is total sampling. The results showed that the factors of Salary, Interpersonal Relations of Coworkers and Promotion Opportunities affect the job satisfaction of nurses in Arifin Achmad Hospital, Riau Province and based on multivariate analysis the dominant variable that affects job satisfaction is the salary variable